Sinkronisasi Sensasi Pendengaran dan Visual di dalam Dunia Simulasi Komputer - Sentagi S. Utami; Mojtaba Navvab; Randy F. Fela (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Current application of virtual environment synthesized by computer simulation still focuses on generating visual cues, while auditory cues has not yet been optimized to create individual movements within the virtual space. Auditory cueing is limited to the ability in detecting the presence of a sound source without further perception. Auralization of variety of spaces with the impact of a variety of architectural elements were synthesized. The auralization data were produced using current computer-simulation technique where both visual and acoustics properties of the room boundaries are considered. Noticeable differences in the auditory cognition of the virtual spaces are measured through the use of subjective evaluation. The acoustical quality are also evaluated utilizing several objective acoustic measures. Diffuser panels were able to increased ability of sound localization up to 12.5% out of the 40 respondents. These panels also increased the speech intelligibility quality, indicated both by the C50 which increased by 89% with 97.5% of respondents approved this condition. Analysis of the subjective and objective measures indicates to what extent the alteration of the simulation is required to create a noticeable auditory cues that enhance the auditory and visual sensation of the virtual space.